Role of Non-Coding RNA in Neurological Complications Associated With Enterovirus 71 - Yang, Feixiang; Zhang, Ning; Chen, Yuxin; Yin, Jiancai; Xu, Muchen; Cheng, Xiang; Ma, Ruyi; Meng, Jialin; Du, Yinan (Frontiers in Cellular and Infection Microbiology, 2022)
Enterovirus 71 (EV71) is the main pathogenic virus that causes hand, foot, and mouse disease (HFMD). Studies report that EV71-induced infections including aseptic meningitis, acute flaccid paralysis and even neurogenic pulmonary edema, can progress to severe neurological complica-tions in infants, young children, and the immunosuppressed population. The mechanism of neurological diseases caused by EV71 has not been fully explored. Non-coding RNA (ncRNA) refers to RNA that does not encode proteins. Previous findings indicate that ncRNAs play a key role in biological processes and disease development associated with EV71. This review summa-rized recent advances concerning the impacts of ncRNAs on neurological diseases caused by in-teraction between EV71 and host, revealing the potential role of ncRNAs in pathogenesis, treatment and diagnosis of EV71-induced neurological complications.